Current status of portal vein thrombosis in Japan: Results of a questionnaire survey by the Japan Society for Portal Hypertension. Issue 4 (14th October 2017) - Kojima, Seiichiro; Watanabe, Norihito; Koizumi, Jun; Kokubu, Shigehiro; Murashima, Naoya; Matsutani, Shoichi; Obara, Katsutoshi
Abstract : Aim: To investigate the current status of portal vein thrombosis (PVT) in Japan, the Clinical Research Committee of the Japan Society of Portal Hypertension undertook a questionnaire survey. Methods: A questionnaire survey of 539 cases of PVT over the previous 10 years was carried out at institutions affiliated with the Board of Trustees of the Japan Society of Portal Hypertension. Results: The most frequent underlying etiology of PVT was liver cirrhosis in 75.3% of patients. Other causes included inflammatory diseases of the hepatobiliary system and the pancreas, malignant tumors, and hematologic diseases. The most frequent site was the main trunk of the portal vein (MPV) in 70.5%, and complete obstruction of the MPV was present in 11.5%. Among the medications for PVT, danaparoid was given to 45.8%, warfarin to 26.2%, heparin to 17.3%, and anti‐thrombin III to 16.9%. Observation of the course was practiced in 22.4%. Factors contributing to therapeutic efficacy were implementation of various medications, thrombi localized to either the right or left portal vein only, non‐complete obstruction of the MPV and Child–Pugh class A liver function. A survival analysis showed that the prognosis was favorable with PVT disappearance regardless of treatment. Conclusion: The questionnaire survey showed the current status of PVT in Japan. Any appropriate medication should be given to a patient with PVT when PVT is recognized. It is necessary to compile a large amount of information and reach a consensus on safe and highly effective management of PVT.